2019
DOI: 10.21608/jappmu.2019.54813
|View full text |Cite
|
Sign up to set email alerts
|

Effect of In-Ovo Injection of Ascorbic, Folic Acids and their Combination on Hachability and Subsequent Growth Performance of Broiler Chicks

Abstract: A total number of 1260 fertile eggs were randomly divided into seven treatments to investigate effect of in ovo-injection of ascorbic, folic acids and their combination at 14 th day of incubation on hatchability and subsequent growth performance of broiler chicks. The experimental design was as follow: 1-Eggs were without injection. 2-Eggs were injected with 0.1ml distiller water/ egg. 3-Eggs were injected with 0.1ml solution containing 6 µg ascorbic acid (AA) /egg. 4-Eggs were injected with 0.1ml solution con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Reported results on hatchability of in ovo delivered FA and EO, are quite variable in the few available literature. Increase ranging from 20 to 29% ( Gouda et al, 2021 , 2022 ), decrease ranging from 2 to 22% ( Abdel-Fattah and Shourrap, 2013 ; Abdel-Halim et al, 2020 ) or unchanged hatchability values have been reported for in ovo delivered FA ( Nouri et al, 2018 ; Ismail et al, 2019 ). Similarly, the few available results on in ovo delivered EO have also reported increase of about 14 to 37% ( Nadia et al, 2008 ; Sulaiman and Tayeb, 2020 ) or no effect of in ovo delivery of EO on hatchability outcomes ( Saki and Salary, 2015 ; Toosi et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reported results on hatchability of in ovo delivered FA and EO, are quite variable in the few available literature. Increase ranging from 20 to 29% ( Gouda et al, 2021 , 2022 ), decrease ranging from 2 to 22% ( Abdel-Fattah and Shourrap, 2013 ; Abdel-Halim et al, 2020 ) or unchanged hatchability values have been reported for in ovo delivered FA ( Nouri et al, 2018 ; Ismail et al, 2019 ). Similarly, the few available results on in ovo delivered EO have also reported increase of about 14 to 37% ( Nadia et al, 2008 ; Sulaiman and Tayeb, 2020 ) or no effect of in ovo delivery of EO on hatchability outcomes ( Saki and Salary, 2015 ; Toosi et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%